2009
DOI: 10.1038/ncpgasthep1356
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of portal hypertensive gastropathy: translating basic research into clinical practice

Abstract: Portal hypertensive gastropathy (PHG) is often seen in patients with portal hypertension, and can lead to transfusion-dependent anemia as well as acute, life-threatening bleeding episodes. This Review focuses on the mechanisms that underlie the pathogenesis of PHG that provide reasonable grounds for the treatment of this condition, and ultimately enable translation of basic research into clinical practice. Increased portal pressure associated with cirrhosis and liver dysfunction is critical for the development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 67 publications
0
30
0
2
Order By: Relevance
“…Portal hypertensive gastropathy (PHG) is a common finding in patients with liver cirrhosis and portal hypertension, and PHG is one of the causes of gastrointestinal blood loss [1][2][3]. The diagnosis is made endoscopically, and the degree of PHG is classified as mild or severe [4].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Portal hypertensive gastropathy (PHG) is a common finding in patients with liver cirrhosis and portal hypertension, and PHG is one of the causes of gastrointestinal blood loss [1][2][3]. The diagnosis is made endoscopically, and the degree of PHG is classified as mild or severe [4].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis is made endoscopically, and the degree of PHG is classified as mild or severe [4]. PHG can progress from mild to severe and vice versa over time, and it has been suggested that various factors, including luminal irritants such as alcohol, bile salts, and non-steroidal anti-inflammatory drugs (NSAIDs), are associated with the progression of PHG [1,2]. However, increased portal pressure and liver dysfunction are critical for the development of PHG in cirrhosis [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hashizume et al [116] reported that cirrhotic patients have dilated small gastric blood vessels, including arterioles, precapillaries, capillaries, submucosal veins, and subserosal veins, with decreased arteriovenous resistance and straightening of arterioles. Percutaneous transhepatic variceal embolization [85] This hyperdynamic circulation impairs gastric mucosal defense mechanisms, causes release of proinflammatory mediators, and inhibits growth factors which render gastric mucosa more susceptible to injury [67,117] and impair mucosal healing [113,114,118,119] . This vulnerable mucosa becomes predisposed to bleeding [117,120] .…”
Section: Pathogenesismentioning
confidence: 99%
“…Percutaneous transhepatic variceal embolization [85] This hyperdynamic circulation impairs gastric mucosal defense mechanisms, causes release of proinflammatory mediators, and inhibits growth factors which render gastric mucosa more susceptible to injury [67,117] and impair mucosal healing [113,114,118,119] . This vulnerable mucosa becomes predisposed to bleeding [117,120] . Decreased gastric mucosal perfusion may explain the increased rate of erosions, ulcers, and bleeding in PHG [118] .…”
Section: Pathogenesismentioning
confidence: 99%